Inhibition of astrocytic differentiation of transplanted neural stem cells by chondroitin sulfate methacrylate hydrogels for the repair of injured spinal cord - Liu, Can; Fan, Lei; Xing, Jianghao; Wang, Qiyou; Lin, Chengkai; Liu, Chang; Deng, Xiaoqian; Ning, Chengyun; Zhou, Lei; Rong, Limin; Liu, Bin (Biomaterials science, 2019)
Neural stem cell (NSC) transplantation exerts a therapeutic effect on spinal cord injury (SCI) but is limited to an unregulated differentiation pattern by which NSCs preferentially differentiate into astrocytes, with relatively few neurons. It is well established that the increased NSC-derived astrocytes exhibit aberrant axonal sprouting associated with allodynia-like symptoms of the forepaws. Some strategies have been used to overcome this issue, such as regulation of major pathways, ex vivo gene transfer, and genetic overexpression. However, lack of efficiency, viral vector safety issues and the risk of tumorigenesis have hindered the clinical application of these treatments. Here, we show that astrocytic differentiation of NSCs in vitro and in vivo can be inhibited by encapsulation of cells in a three-dimensional chondroitin sulfate methacrylate (CSMA) hydrogel. When CSMA hydrogels were used to transplant NSCs, the combinatory implant promoted functional recovery and attenuated the hypersensitivity responses of the forepaws. Further analysis showed that transplantation of NSCs within CSMA hydrogels reduced injured cavity areas and promoted neurogenesis rather than fibroglial formation after graft implantation. Furthermore, the treatment prevented allodynia-related CGRP/GAP43-positive nociception due to fibers sprouting into inappropriate lamina regions. Taken together, these findings show that CSMA/NSCs combined transplantation helps prevent adverse side effects of NSCs treatment and promotes recovery of SCI. Recovery from spinal cord injuries after transplanted neural stem cells encapsulated in chondroitin sulfate methacrylate hydrogels.